Ground Fall Injuries In Underground Stone Mines – Summary (The National Institute for Occupational Safety and Health (NIOSH), 2003)
Workers in underground stone mines have a high fatality rate caused by falls of ground from the mine roof or rib. NIOSH recommendations to reduce ground fall injuries and deaths address baskets, mechanical scalers, mechanical bolters, drill steel changing, personal protective equipment, and training. Description of Exposure An informal National Institute for Occupational Safety and Health (NIOSH) review in 1998 identified approximately 17 new underground limestone operations in vari¬ous stages of planning; as many as 35 new underground stone mines are expected by 2005. Many of these new underground stone mines will employ new or inexperienced workers with minimal knowledge of the hazardous conditions that exist underground. Workers in underground stone mines have a fatality rate nearly 20 times that of workers in the manufacturing sector. Three quarters of the fatalities in underground stone mines are caused by falls of ground from the mine roof or rib (Figure 1) [Statistical Abstract of the United States 1985-1999; MSHA 1983-1999]. During 1983-1999, nonfatal ground falls resulted in 140 injuries, or 15% of all underground, lost time stone mine injuries. These nonfatal ground fall injuries resulted in more than 13,800 lost workdays (one third of all lost workdays). Ground falls generate more disabling injuries and time away from work than any other type of incident. [ ]